Concurrent spindle-cell thymoma and thymic cysts in a Barbary sheep (Ammotragus lervia): case report and review of the literature. (November 2016) - Li, Wen-Ta; Chang, Hui-Wen; Jeng, Chian-Ren; Liu, Chen-Hsuan; Wang, Fun-In; Chang, Li-Jen; Pang, Victor Fei
An ~21-year-old female Barbary sheep ( Ammotragus lervia ) died spontaneously following a lengthy episode of difficulty in walking. An ~6 × 3 × 3 cm, unilocular cystic growth was found in the cranioventral thorax. The fibrotic cystic wall, lined by a single layer of flattened to cuboidal epithelial cells, was invaginated and partially encircled solid masses of fusiform neoplastic cells with multiple intratumoral cystic structures. The fusiform neoplastic cells were intensely positive for cytokeratin (CK) and partially positive for α–smooth muscle actin and vimentin, but negative for thyroid transcription factor–1 (TTF-1) and neuron-specific enolase (NSE). The intratumoral cysts were lined by CK-positive but TTF-1– negative, NSE-negative, flattened, cuboidal to columnar epithelial cells, suggestive of cystically dilated medullary duct epithelium-derived structures. Based on the location and histopathologic findings of the growth, concurrent spindle-cell thymoma and thymic cysts was diagnosed. We also discuss the correlation between thymic cysts and thymoma and review the literature of thymomas in ovine and wildlife species.